Occupational exposure to cytotoxic drugs - Viegas , Susana (2018)
Healthcare workers who prepare or administer cytotoxic agents run the risk of exposure, and the risks for health are real even at doses lower than those applied in cancer patients, because, in theory, no dose is safe. The most common and problematic route of exposure is through the skin, especially as work surfaces can remain contaminated even after cleaning. This pilot study aimed to demonstrate the importance of having an effective surface decontamination protocol by determining surface contamination with cyclophosphamide, 5-fluorouracil, and paclitaxel as the most common cytotoxic drugs in an oncology day service. Samples were collected before and after drug handling and analysed with high performance liquid chromatography with diode array detection (HPLC-DAD). Of the 29 samples collected before drug handling 23 were contaminated, five of which with more than one drug. Of the 30 samples collected after drug handling 25 were contaminated, eight of which with more than one drug. The two time points did not significantly differ, which evidences a widespread contamination and ineffective cleaning. This calls for revising the cleaning protocol and handling procedure to place contamination under control as much as possible.